2002
DOI: 10.1046/j.1365-2036.2003.01392.x
|View full text |Cite
|
Sign up to set email alerts
|

Mercaptopurine metabolite results in clinical gastroenterology practice

Abstract: SUMMARYBackground: Azathioprine (AZA) and its active metabolite mercaptopurine (MP) are frequently used in the management of inflammatory bowel disease. Measurement of the AZA ⁄ MP metabolites, thioguanine (TG) and methylmercaptopurine (MMP), has been suggested as a means to optimize therapy with AZA ⁄ MP in inflammatory bowel disease. Aim: To evaluate the results of initial AZA ⁄ MP metabolite panels sent by gastroenterologists during the first year of its widespread availability. Methods: Initial AZA ⁄ MP me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 23 publications
5
32
0
2
Order By: Relevance
“…Similar results were also seen in a recent study performed in a small series of pediatric IBD patients, with self-reported rates of "complete adherence" of 70% and 43%, for immunomodulators and aminosalicylates, respectively [16]. In a observational study, Bloomfeld and Onken [17] reported the initial azathioprine/6-mercaptopurine metabolite levels of 9187 patients with digestive diseases. In this large series, only 3% of patients had undetectable levels of metabolites, suggesting noncompliance to treatment; however, 46% of patients were underdosed, resulting from an inadequate prescribed regimen by the doctor or an inadequate patient compliance [17].…”
Section: Discussionsupporting
confidence: 79%
“…Similar results were also seen in a recent study performed in a small series of pediatric IBD patients, with self-reported rates of "complete adherence" of 70% and 43%, for immunomodulators and aminosalicylates, respectively [16]. In a observational study, Bloomfeld and Onken [17] reported the initial azathioprine/6-mercaptopurine metabolite levels of 9187 patients with digestive diseases. In this large series, only 3% of patients had undetectable levels of metabolites, suggesting noncompliance to treatment; however, 46% of patients were underdosed, resulting from an inadequate prescribed regimen by the doctor or an inadequate patient compliance [17].…”
Section: Discussionsupporting
confidence: 79%
“…Why a relatively low mean dose was being used for azathioprine (but not for 6-MP) is uncertain, but has been a consistent finding in audits of its use where thiopurine metabolite estimations were not available. 21,22 There was no history of previous neutropenia or abnormal liver function tests resulting in a dose reduction in any of the subjects. Therefore, a failure by the treating physicians to maximize the dose is a more likely explanation.…”
Section: Discussionmentioning
confidence: 99%
“…20 In these patients, determination of both 6-TGN and 6-MMP can define different clinical scenarios, identify why patients are not responding, and guide decisions regarding treatment. Audits of the use of thiopurines in hospital clinics (in centers without access to metabolite testing) show the tendency for dosage lower than the recommended 2-2.5 mg/kg for azathioprine and 1-1.5 mg/kg for 6-MP, 21,22 suggesting the potential for metabolite testing to improve clinical practice. However, there remains controversy about its true value, with counterclaims that it contributes little to good clinical practice.…”
mentioning
confidence: 99%
“…[4][5][6][7][8] For azathioprine (AZA) and/or mercaptopurine (MP), nonadherence rates range from 3%-64.7%. [9][10][11][12] Anti-tumor necrosis factor (TNF) therapy has changed the treatment of CD that is refractory to standard medications. 13 Three anti-TNF agents, namely, infliximab, adalimumab, and certolizumab pegol, have shown efficacy in treating luminal CD.…”
Section: (Inflamm Bowel Dis 2011;17:152-159)mentioning
confidence: 99%